A special setting serving the psychoanalytical method in the analysis of an adolescent girl - Minerbo, Marion (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
This is the narrative of an analysis that became possible when my clogs became part of the transferential field. This fact does oblige us to problema-tize the concept of transference as "inter-subjective relahtionship ", as well as the idea of a setting stablished from outside the analytic process, that is, regardless of the transferer]tial diagnosis.